The Influence of Information Services and Educational Strategies on The Public's Understanding of Drugs - Pravitasari, Endyastuti; Pamungkas, Gina Ayu (Riviera Publishing, 2023)
This study aims to examine and analyze the influence of information services and educational strategies at the level of understanding with social media as a moderating variable. The population in this study used a sample of 238 respondents who were people from North Jakarta through sub-districts, namely, Cilincing, Koja, Kelapa Gading, Pademangan, Penjaringan, and Tanjung Priok. Data collection techniques by distributing research questionnaires in the form of Google Forms through social media. The data processing method in this study uses SmartPLS software which is used to test the hypothesis. The results of this study show that information services have a positive and significant effect on the level of understanding. Educational strategies have a positive and significant effect on the level of understanding. Social media has a positive and significant effect on the level of understanding. Social media weakens but influences and can moderate between information services at the level of understanding. Social media can reinforce and moderate educational strategies to the level of understanding. The research is recommended if BNN Kota North Jakarta wants to increase the level of statements, it is suggested that it can improve service quality and ensure that all content creation processes follow increasing trends and there are educational values in the content.